Molecular docking and evaluation of antileishmania activity of a ruthenium complex with epiisopiloturine and nitric oxide - Araújo, Joabe Lima (2020)
Leishmaniasis is an infectious disease that affects both animals and humans, caused by flagellated parasites belonging to the genus Leishmania. The disease is estimated to reach about 700,000 to 1 million people, causing the deaths of 20 to 30,000 individuals annually. Thus, the present study aims to perform molecular docking tests and evaluation of antileishmania activity in vitro of a ruthenium complex with epiisopiloturine and nitric oxide. AutoDockTools-1.5.6 software was used to perform molecular docking tests. Molecular targets were considered rigid, and Epiruno2 considered flexible. The genetic algorithm Lamarckian (AGL) with global search and pseudo-Solis and Wets with local search were the methods adopted in the docking. The most promising results of molecular interaction were achieved in the targets Pteridine reductase and UDP-glucose Pyrophosphorylase with rates of -10.68 Kcal·mol-1 and -10.51 Kcal·mol-1, respectively. This demonstrates that Epiruno2 has molecular affinity with the targets of L. major. In vitro assays prove the antileishmania activity of the complex in the face of promastigote forms with inhibition of growth, concluding through this study that the Epiruno2 complex has antileishmania activity.